RELIGIOUS AND MORAL APPROACH TO SEX EDUCATION OF CHILDREN AND ADOLESCENTS (THE BEGINNING OF THE XX CENTURY) - Onupchenko, Oksana (Social work and education, 2017)
The author examined the religious and moral approach to the sexual education of children and adolescents, which determines the basis of the relationship between man and woman, which has been dominant for centuries both in Western Europe and in the conditions of Orthodox Russia. Christianity gradually came to consider sexual relations primarily as a necessity related to childbearing and procreation. Demanding the flock of moral purity of thoughts and restraint of sensual manifestations, the church did not encourage the premature enlightenment of children and adolescents in sexual matters. The result of this approach for a long time was that children practically did not get even elementary knowledge in the family at this field, there was no medical and hygienic enlightenment, the matter was limited only to the requirements of moral and ethical purity and observance of the commandments of God.Representatives of the same Christian-Orthodox direction (I. Sikorsky, I. Skvortsov, E. Nakashidze, E. Lozinsky and others) did not allow early development of sensuality of children, and especially in the sexual sphere. They believed that correct sexual education is possible only on the basis of Christian consciousness. The main conditions for the "successful struggle against the low-lying manifestations" in the sphere of sexual life, they called internal and external discipline, and sexual education was built on the basis of direct prohibitions, with the establishment of premarital chastity and asceticism.Giving advice on how a child could protect himself from the many dangers of premature awakening of sexual life, they pay attention to the internal and external discipline. The main emphasis of internal discipline advocates of the religious approach put the appeal to Christ, and the external discipline is to observe the following tips: extreme caution in choosing books that direct the imagination towards sensuality; stimulation of intellectual interest through familiarity with the sciences in general and a special passion for one of them. And also some basic tips on sexual hygiene: enough fresh air during the day and at night, bathing, comprehensive physical exercises, simple and active way of life, meaningful and expedient work, moderation and regularity in food, lack of everything exciting - even coffee and tea etc...